2003
DOI: 10.1007/s00114-003-0469-5
|View full text |Cite
|
Sign up to set email alerts
|

Methyl 2-(methylthio)benzoate: the unique sulfur-containing sex pheromone of Phyllophaga crinita

Abstract: The female-produced sex pheromone of Phyllophaga crinita (Burmeister) (Coleoptera: Scarabaeidae: Melolonthinae; the adult has no common name) is identified as methyl 2-(methylthio)benzoate. This is the first identification of a sulfur-containing, long-distance, female-produced sex attractant from any insect taxa. The root-feeding larvae of this species are serious pests in many crops in Texas and Mexico. In field tests, many P. crinita males were captured in traps baited with the authentic compound. Interestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 18 publications
0
16
1
Order By: Relevance
“…The air stream carried the column effluent over the beetle antennal preparation. See Robbins et al (2003) for a photograph of the beetle antennal preparation. The output signal from the antenna was amplified by a customized single-step highinput impedance DC amplifier.…”
Section: Methodsmentioning
confidence: 99%
“…The air stream carried the column effluent over the beetle antennal preparation. See Robbins et al (2003) for a photograph of the beetle antennal preparation. The output signal from the antenna was amplified by a customized single-step highinput impedance DC amplifier.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, insect use of sulfur-containing semiochemicals has been found in only a few species. Robbins et al (2003) reported methyl 2-(methylthio)benzoate as a unique sulfurcontaining sex pheromone for a scarab beetle, Phyllophaga crinita. Sulfur-containing components of the sex pheromone of the cockroach Nauphoeta cinerea are 2-methylthiazolidine and 2-methyl-2-thiazoline (Sreng 1990;Sirugue et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…The sex pheromone of Phyllophaga crinita was identified as methyl 2-(methylthio)benzoate (Robbins et al 2003). Interestingly, Coca-Abia (2002) has recently resurrected the genus Trichesthes and removed P.…”
Section: Discussionmentioning
confidence: 99%